Ciprofloxacin resistance among Campylobacter jejuni isolates obtained from shelter dogs in Texas. (9th December 2018) - LaLonde‐Paul, Denise; Cummings, Kevin J.; Rodriguez‐Rivera, Lorraine D.; Wu, Jing; Lawhon, Sara D.
Abstract: There are few epidemiologic studies on the shedding of Campylobacter among dogs in the United States, despite the potential public health implications. Our objectives were to estimate the prevalence of faecal Campylobacter shedding among Texas shelter dogs as detected by culture methods and to characterize the isolates by species and antimicrobial susceptibility. Using a cross‐sectional study design, faecal samples were collected from 185 dogs in six animal shelters throughout Texas between May and December 2014. Four culture methods were used to isolate Campylobacter from samples, and isolates were characterized. The prevalence of Campylobacter shedding was 45.4% (84/185; 95% CI, 38.1%–52.9%). Of 294 isolates from the 84 positive dogs, 26 (8.8%) isolates from seven dogs were identified as Campylobacter jejuni . Two of the isolates from one dog demonstrated resistance to ciprofloxacin and nalidixic acid. Direct plating on mCCDA‐CAT agar without enrichment identified the highest number of positive dogs (62%; 52/84). Incidence of ciprofloxacin‐resistant Campylobacter infections among humans has increased over the last several years. Canine shedding of Campylobacter is a potential source of zoonotic transmission.